Position-related content acquisition for CCM. Issue 4 (11th November 2021) - Li, Yanli; Wang, Xiaonan
The Content-Centric Networking (CCN) depends on reverse paths and limited broadcast to achieve content acquisition, but the reverse-path disruption due to node mobility leads to content acquisition failures and flooding results in considerable content acquisition costs. In this paper, we propose a Unicast-based content acquisition scheme for Content-Centric MANET (UCCM) to reduce content acquisition costs and improve success rates. UCCM employs the address-centric unicast instead of the content-centric broadcast to achieve the content acquisition, so the content acquisition cost is lowered. Moreover, a requester acquires the content from the nearest provider in the address-centric unicast way, so the content is returned to a requester based on the requester's address rather than the reverse paths. UCCM is evaluated, and the analysis results show that UCCM reduces the content acquisition cost by nearly 63.8% and improve the success rate by nearly 5.9%.